Missiology an introduction to the foundations, history and strategies of world mission - Terry, John Mark, 1949-; Smith, Ebbie C.; Anderson, Justice, 1929- (Nashville, TN Broadman and Holman, 1998)
Includes bibliographical references and index.
Keywords: Missions; Southern Baptist Convention -- Missions; Baptists -- missions